12-Year longitudinal study linking within-person changes in work and family transitions and workplace injury risk. (December 2020) - Kramer, Amit; Cho, Seonghee; Gajendran, Ravi S.
Highlights: We study the association of work-family demands and resources with workplace injuries. We use 12-year longitudinal data to test our hypotheses. A within-person change in work hours is positively associated with an increased risk of injury. A within-person change in spouse work hours is positively associated with an increased risk of injury. A within-person change in number of children is positively associated with an increased risk of injury. Abstract: Introduction: Despite the rich tradition of research on predictors of workplace injury, most studies rely on cross-sectional, between-person designs. Furthermore, prior research has often overlooked the possibility that factors outside the work domain can influence the occurrence of actual injuries at work. To address these limitations, the current study examined the effects of work and family demands on the occurrence of workplace injury. Drawing on the intuition of the work-home resources model (W-HR), we investigated how within-person level changes in demands and resources from both domains influence work injuries over a 12-year period. Method: We used 12 years of longitudinal data ( N  = 7, 820) to study the long-term within-person changes in work and family domains and to capture the event of low frequency incidence such as workplace injury. Specifically, we conducted multilevel analyses to study the links between within-person change in time and energy resources both in work and family domains and within-person change in the likelihood of experiencing a workplace injury. Results and conclusion: The findings showed that within-person changes in work hours, spousal work hours, income and number of children, were significantly associated with changes in the likelihood of experiencing a workplace injury. We conclude with a discussion of implications for theory and future research of workplace injuries. Practical application: The research provided useful insights on the intimate association between work and family domains in the context of safety management.